Relationship Between Accommodation Insufficiency, Screen Time, and Asthenopia Symptoms in Young Adult Patients - Muhammad Akbar Wicaksana; Sirait, Susanti Natalya (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background: Asthenopia, characterized by symptoms following near visual activity, often affects individuals with accommodative insufficiency and prolonged screen time. This study aims to investigate the correlation between demographic, refractive status, accommodative insufficiency, screen time, and asthenopia symptoms among patients at the Indonesia National Eye Centre, Cicendo Eye Hospital Bandung, Indonesia. Method: In this cross-sectional study, consecutive sampling was conducted to obtain subjects. Ocular examinations were performed to determine refractive status, amplitude of accommodation, accommodative insufficiency, symptoms of asthenopia, and screen time. Result: A total of 105 subjects were included in the study, with a median age of 25 years (IQR: 3). The median amplitude of accommodation was 9.09 D (IQR: 0.7), which was found to be lower than normative data. Asthenopia was observed in 47 subjects (44.7%), and accommodative insufficiency was present in 37 subjects (35.2%). Male gender and screen time > 8 hours per day were significantly correlated with asthenopia (p=0.048 and p<0.001, respectively), while refractive status and accommodative insufficiency showed no significant correlation. Conclusion: this study demonstrates a relatively similar prevalence of asthenopia. Additionally, male gender and excessive screen time were identified as risk factors for asthenopia. Keywords: Amplitude of Accommodation, Screen Time, Asthenopia.